A rare case of juvenile amyotrophic lateral sclerosis - Bodur, Muhittin; Toker, Rabia Tütüncü; Başak, Ayşe Nazlı; Okan, Mehmet Sait (The Turkish Journal of Pediatrics, 2021)
Background. Amyotrophic lateral sclerosis (ALS) is a chronic motor neuron disease characterised by progressive weakness in striated muscles resulting from the destruction of neuronal cells. The term juvenile ALS (JALS) is used for patients whose symptoms start before 25 years of age. JALS may be sporadic or familial. Case. Here, we present a sporadic case of JALS because of its rarity in children. The heterozygous p.Pro525Leu (c.1574C > T) variation was identified in the fused in sarcoma (FUS) gene. Conclusion. The p.Pro525Leu mutation in the FUS gene has been detected in patients with ALS, characterised by early onset and a severely progressive course.